Assessing Reserve Adequacy. (Policy Papers; Policy Paper ;, 2011)
The dramatic increase in reserves holdings over the past decade has resumed since the global financial crisis, even at an accelerated pace. While the crisis has heightened perceptions of the importance of holding adequate reserves, there is little consensus on what constitutes an adequate level from a precautionary perspective: traditional metrics are narrowly-based and often provide conflicting signals; while newer approaches tend to be hostage to stylized modeling assumptions and calibrations. As a result, assessments tend to rely on comparisons with peers, probably amplifying the upward trend as perceived needs rise in line with actual holdings.